Right iliac vein tumor - Praderi, Raúl; Vercelli, Jorge; Praderi, José; Malfatto, Gustavo; Vergara, Hugo; Zimmer, Walter (Cirugía del Uruguay, 1993)
The authors reports the brief clinical history and tomographic diagnosis of what finally turned out to be a leiomyoma of the external right iliac vein. lt was resected and the permeability of the vascular axis was maintained.